Pengaruh Motivasi, Promosi Jabatan Dan Kompensasi Terhadap Kinerja Karyawan PT. Bank Negara Indonesia.Tbk KC Jambi - Mohd. Iqbal Fazliawinata; Heriyani (Journal of Applied Accounting And Business, 2021)
This study aims to analyze the influence of motivation, job promotion and employee performance compensation at PT Bank Negara Indonesia (Persero) Tbk. This study uses a questionnaire as an instrument to take a sample of 50 respondents. The sampling method used was nonprobability sampling. The analytical method used in this research is multiple linear regression analysis. The independent variables in this study, namely motivation, promotion and compensation, explain the dependent variable, namely the employee's performance of 99.6% and the remaining 04% or determined by other variables not included in this analysis or research. The results of this study indicate that motivation, promotion and position have a significant effect on employee performance because they have a significance value <0.05. Abstract is basically an English version of abstrak. All components in abstract are written in the same style as in abstrak. The word “Abstract” and the paragraph is written in Italics.